Exploring time, tense, and aspect in natural language database interfaces - Androutsopoulos, Ion (Natural language processing (Amsterdam, Netherlands), 2002)
Advances in temporal databases make it increasingly easier to store time-dependent information, creating a need for facilities that will help end-users access this information. In the context of natural language interaction, significant effort has been devoted to interfaces that allow database queries to be formulated in natural language. Most of the existing interfaces, however, do not support adequately the notion of time. Drawing upon tense and aspect theories, temporal logics, and temporal databases, this cross-discipline book examines relevant issues from the three areas, developing a uni.